Environmental and biological monitoring of PAHs exposure in coke-oven workers at the Taranto plant compared to two groups from the general population of Apulia, Italy / Monitoraggio ambientale e biologico dell’esposizione a IPA nei lavoratori della... - Campo, Laura; Vimercati, L.; Carrus, A.; Bisceglia, Lucia; Pesatori, Angela Cecilia; Bertazzi, P.A.; Assennato, G.; Fustinoni, Silvia (La Medicina del Lavoro, 2012)
Summary Background: Polycyclic aromatic hydrocarbons (PAHs) exposure in the coke industry poses a risk for workers’ health as well as for subjects living in the plant vicinity. Objectives: To assess PAHs exposure in coke-oven workers (CW) at the Taranto plant, Apulia, and in subjects from the general population living near (NC) and far away (FC) from the plant. Methods: Exposure was assessed by personal air sampling and urinary 1-hydroxypyrene (1-OHP) measured in 100 CW, 18 NC and 15 FC. Results: Median airborne benzo[a]pyrene (BaP) levels were 152, 1.5, and 3.6 ng/m3 in CW, NC, and FC, respectively. In CW, median 1-OHP increased from 1.45 to 1.96 mg/g creatinine (crt) during the work shift (p>0.05); in NC and FC, 1-OHP levels were 0.56 and 0.53 mg/g crt. No significant differences between NC and FC for both air and urinary indices were found. BaP exposure in CW exceeded the recently proposed German acceptable (70 ng/m3) and tolerable (700 ng/m3) risk-based limit values in 82 and 11% of subjects, respectively. In NC and FC, BaP exposure exceeded the European target value for ambient air (1 ng/m3) in 67 and 60% of subjects, respectively. Biomonitoring showed that 21% of CW had 1-OHP levels higher than the proposed biological limit value for the coke-oven industry (4.4 mg/g crt), while 93% of FC, and 88% of NC, had 1-OHP levels exceeding the Italian reference value (0.3 mg/g crt). Among non-smokers, a linear regression between 1-OHP and BaP (Pearson value r=0.65, p<0.05) allowed us to estimate levels of 1.2 and 1.9 mg/g crt for 1-OHP end-of-shift corresponding to acceptable and tolerable limit values. Conclusions: Although lower than in the past, PAHs exposure in the coke plant still poses a health risk for workers and the general population and requires further efforts to improve workplace conditions. Riassunto «Monitoraggio ambientale e biologico dell’esposizione a IPA nei lavoratori della cokeria di Taranto e in due gruppi della popolazione generale pugliese». Introduzione: L’esposizione a idrocarburi policiclici aromatici (IPA) provenienti dall’industria della produzione del coke pone un potenziale rischio per la salute dei lavoratori e per i soggetti della popolazione generale. Obiettivi: Valutare l’esposizione a IPA in lavoratori della cokeria (CW) di Taranto, Puglia, e in soggetti della popolazione che vivono nelle vicinanze dell’impianto (NC) o a distanza da esso (FC). Metodi: L’esposizione a IPA è stata studiata mediante campionamento personale ambientale e misura di 1-idrossipirene urinario (1-OHP) in 100 CW, 18 NC e 15 FC. Risultati: L’esposizione mediana a benzo[a]pirene (BaP) è risultata 152, 1,5, e 3,6 ng/m3 rispettivamente nei CW, NC e FC. Nei CW, 1-OHP aumentava durante il turno di lavoro da 1,45 a 1,96 mg/g creatinina (crt) (p>0,05); nei NC e FC, i livelli 1-OHP erano 0,56 e 0,53 mg/g crt. Non è stata trovata alcuna differenza tra NC e FC, sia per l’esposizione ambientale che per i valori di 1-OHP. L’esposizione a BaP superava il valore limite di rischio accettabile (70 ng/m3) e tollerabile (700 ng/m3) proposti recentemente in Germania, nell’82 e nell’11% dei CW. Il 67% e il 60% dei NC e FC superava il valore obiettivo europeo per la qualità dell’aria (1 ng/m3). Il 21% dei CW aveva livelli di 1-OHP più alti del valore limite biologico proposto per l’industria del coke (4,4 mg/g crt), mentre il 93% dei FC e l’88% dei NC aveva valori di 1-OHP eccedenti i valori di riferimento della popolazione italiana (0,3 mg/g crt). Nei soggetti non fumatori, la regressione lineare tra 1-OHP e BaP (r=0,65, p<0.05) ha permesso di calcolare livelli di 1,2 e 1,9 mg/g crt per 1-OHP (fine turno) corrispondenti ai valori limite di rischio accettabile e tollerabile. Conclusioni: Benché più bassa che in passato, l’esposi-zione a IPA derivante dalla cokeria pone ancora un rischio per la salute dei lavoratori e della popolazione generale e richiede ulteriori sforzi per migliorare le condizioni igieniche di questo ambiente di lavoro.